Sustainability in start-up ventures: what founders say versus what they do - Galpin, T; Hebard, J (Emerald, 2015)
Founders of start-up ventures today can benefit from implementing sustainability efforts to enhance their viability over the long term. But, do founders of start-up ventures regularly incorporate and reinforce sustainable business practices in their business models? An opinion survey of prospective business start-up founders, along with a content analysis of their business plans, is used to compare founders’ views – “what they say” – about sustainable business practices to their described business models – “what they do.” Findings suggest that prospective business founders do value sustainable business practices. However, the content of their business models does not reflect their espoused importance of sustainability.